Sexual Knowledge : Feeling, Fact, and Social Reform in Vienna, 1900-1934. - McEwen, Britta (Austrian and Habsburg studies., 2012)
Vienna's unique intellectual, political, and religious traditions had a powerful impact on the transformation of sexual knowledge in the early twentieth century. Whereas turn-of-the-century sexology, as practiced in Vienna as a medical science, sought to classify and heal individuals, during the interwar years, sexual knowledge was employed by a variety of actors to heal the social body: the truncated, diseased, and impoverished population of the newly created Republic of Austria. Based on rich source material, this book charts cultural changes that are hallmarks of the modern era, such as the.